Physicochemical and biological characterization of a xanthan gum-polyvinylpyrrolidone hydrogel obtained by gamma irradiation - López-Huante, Tania; Del Prado-Audelo, María L.; Caballero-Florán, Isaac H.; Reyes-Hernández, Octavio D.; Figueroa-González, Gabriela; González-Del Carmen, Manuel; Giraldo-Gomez, David M.; Sharifi-Rad, Javad; González-Torres, Maykel; Cortes, Hernán; Leyva-Gómez, Gerardo (Cellular and Molecular Biology, 2021)
Xanthan gum (XG) and polyvinylpyrrolidone (PVP) are two polymers with low toxicity, high biocompatibility, biodegradability, and high hydrophilicity, making them promising candidates for multiple medical aspects. The present work aimed to synthesize a hydrogel from a mixture of XG and PVP and crosslinked by gamma irradiation. We assessed the hydrogel through a series of physicochemical (FT-IR, TGA, SEM, and percentage of swelling) and biological (stability of the hydrogel in cell culture medium) methods that allowed to determine its applicability. The structural evaluation by infrared spectrum demonstrated that a crosslinked hydrogel was obtained from the combination of polymers. The calorimetric test and swelling percentage confirmed the formation of the bonds responsible for the crosslinked structure. The calorimetric test evidenced that the hydrogel was resistant to decomposition in contrast to non- irradiated material. The determination of the swelling degree showed constant behavior over time, indicating a structure resistant to hydrolysis. This phenomenon also occurred during the test of stability in a cell culture medium. Additionally, microscopic analysis of the sample revealed an amorphous matrix with the presence of porosity. Thus, the findings reveal the synthesis of a novel material that has desirable attributes for its potential application in pharmaceutical and biomedical areas.